PENGARUH DAYA TARIK TRANSIT ADVERTISING DAN KREDIBILITAS BRAND AMBASSADOR TERHADAP MINAT BELI COLLAGENA - Lukito Mughni Purwanto; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
PT Mayora Indah Tbk launched Collagena as the first ready-to-drink sterilized milk product in Indonesia containing 1,000 mg of collagen. As a new product still in the introduction stage, Collagena faces challenges in building consumer awareness and purchase intention. In its marketing strategy, Collagena utilizes transit advertising and brand ambassador Song Hye Kyo. Awareness of Collagena based on Brand24 data shows positive growth, while previous studies have demonstrated that transit advertising and brand ambassadors influence purchase intention. However, Collagena has not yet entered the list of competing brands in the ready-to drink sterilized milk category based on the Top Brand Index. This condition raises questions regarding the effectiveness of the marketing strategies implemented, particularly in building purchase intention for a new product such as Collagena, considering that most previous studies were conducted on well-established products. This study employed a quantitative explanatory approach through questionnaires distributed to 106 respondents in the Greater Jakarta area who had been exposed to Collagena marketing. The data were analyzed using simple linear regression. The results indicate that the attractiveness of transit advertising and the credibility of the brand ambassador partially have a positive and significant effect on Collagena purchase intention. Therefore, both marketing strategies are considered effe